Analysis of Positive Discipline Implementation Strategy through Technology Utilization in Providing Feedback to Parents of Students - Apiri, Enton (PPSDP International Journal of Education, 2024)
This research aims to analyze strategies for implementing positive discipline through the use of technology in providing feedback to students' parents. Positive discipline emphasizes the development of constructive behavior through a dialogue and empathy approach, not repressive punishment. However, one of the challenges in implementing this discipline is the lack of effective communication between schools and parents, which is often caused by limited time and access. In the digital era, technology offers innovative solutions to overcome this problem by facilitating the provision of fast and real-time feedback through school applications, digital platforms and instant messaging. This research uses a qualitative approach with a case study method in schools that implement positive discipline. Data was collected through in-depth interviews, participant observation, and documentation from teachers and parents. The research results show that technology can increase the effectiveness of communication between schools and parents, allowing parents to monitor student behavior developments more efficiently. Technology also provides easier access for parents to get involved in supporting children's positive behavior at home, which in turn strengthens positive discipline at school. However, this research also identified several challenges, including gaps in technology access among parents, data security and privacy issues, and the potential for reducing the quality of personal interactions between teachers and parents. Therefore, it is important to develop inclusive and safe communication strategies to ensure optimal parental involvement. This research contributes to the development of a technology-based positive discipline approach, which it is hoped will be implemented more widely in schools, particularly in the context of increasing parental involvement and the efficiency of feedback provided.